Periode Kritis Jagung Manis Berkompetisi dengan Gulma Pada Entosil Lombok Tengah - I Ketut Ngawit; M Taufik Fauzi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Weeds are not always detrimental to plants, because there is a period of time when they are most influential on plant growth and yield and a period of time when weeds are present is called critical piriode. A research aimed to determine the critical period of sweet corn with weeds in Central Lombok entisoles. The experimental research method with experiments in the field used a randomized block design (RBD), which consisted of 12 treatments, weed-free plants (TBG) from planting to age, 10;20;30;40;50 and 60 days and the plants were allowed to roll (TG). since planting until the age of 10;20; 30; 40;50 and 60 days. The results showed that the presence of tolerable weeds on sweet corn plants was only until the age of 30 days after planting. Weeds must be weeded after the plants are between 30-40 days old, if done after the plants are 40 days old, the crop yields cannot be saved. The critical period for sweet corn competing with weeds on the Lombok Tengan entisol is in the age range between 30-40 days after planting. Plants that compete with weeds for 40, 50, and 60 days after planting (until harvest) experience a decrease in yield of 60.32%, 82.84% and 98.66%. Meanwhile, plants that did not compete (weed free) for only 10, 20 and 30 days experienced a decrease in yield of 98.61%, 80.16% and 61.40%.